2013
DOI: 10.1103/physrevb.87.024111
|View full text |Cite
|
Sign up to set email alerts
|

Large built-in electric fields due to flexoelectricity in compositionally graded ferroelectric thin films

Abstract: TitleLarge built-in electric fields due to flexoelectricity in compositionally graded ferroelectric thin films We investigate the origin of large built-in electric fields that have been reported in compositionally graded ferroelectric thin films using PbZr 1−x Ti x O 3 (0.2 < x < 0.8) as a model system. We show that the built-in electric fields that cause a voltage offset in the hysteresis loops are dependent on strain relaxation (through misfit dislocation formation) and the accompanying polarization distribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
44
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(47 citation statements)
references
References 41 publications
2
44
1
Order By: Relevance
“…Again, it is assumed that the thermodynamic, elastic, and electromechanical coefficients of the compositionally graded Ba 1−x Sr x TiO 3 films are a linear function of z determined from a weighted average of the coefficients for BaTiO 3 and SrTiO 3 given in Sec. II A consistent with prior work [59].…”
Section: Boundary Conditions Is Expressed Asmentioning
confidence: 99%
See 3 more Smart Citations
“…Again, it is assumed that the thermodynamic, elastic, and electromechanical coefficients of the compositionally graded Ba 1−x Sr x TiO 3 films are a linear function of z determined from a weighted average of the coefficients for BaTiO 3 and SrTiO 3 given in Sec. II A consistent with prior work [59].…”
Section: Boundary Conditions Is Expressed Asmentioning
confidence: 99%
“…In contrast to their homogeneous counterparts, compositionally graded ferroelectrics exhibit self-poling [1], built-in potentials [2], asymmetric or shifted hysteresis loop [3], and the potential for geometric frustration [4]. Their distinctive electric-field, thermal, and stress susceptibilities make such systems potentially important for a range of devices [2].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The work in Ref. 15 showed that flexoelectricity plays an important role in increasing the pyroelectric property of graded ferroelectric materials and 16 investigated the large built-in electric fields in graded ferroelectric thin films due to flexoelectric coupling. In our previous work, 5 we have computationally demonstrated the possibility of designing such composites through suitable topologies, material property differences, and the selection of optimum feature sizes.…”
mentioning
confidence: 99%